Deciphering the immunosuppressive tumor microenvironment in ALK- and EGFR-positive lung adenocarcinoma - Budczies, Jan; Kirchner, Martina; Kluck, Klaus; Kazdal, Daniel; Glade, Julia; Allgäuer, Michael; Kriegsmann, Mark; Heußel, Claus Peter; Herth, Felix; Winter, Hauke; Meister, Michael; Muley, Thomas; et al. (Cancer immunology immunotherapy, 2021)
The advent of immune checkpoint blockade (ICB) has led to significantly improved disease outcome in lung adenocarcinoma (ADC), but response of ALK/EGFR-positive tumors to immune therapy is limited. The underlying immune biology is incompletely understood.
Gesehen am 05.05.2023